Peran Guru Pendidikan Agama Islam dalam Membentuk Budaya Toleransi dan Kerukunan Umat Beragama di Akademi Maritim Cirebon - Muslih, Muhammad; Muhibudin, Agus (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the role of Islamic religious education teachers in fostering an attitude of religious tolerance at the Cirebon Maritime Academy. This type of research is qualitative research. The subjects of this study were the Head of the Study Program, Lecturer of Citizenship, Lecturer of Religion. Data collection techniques in this study were carried out using observation, interview, and documentation methods. Based on the results of the study, it is known that the role of schools in building an attitude of religious tolerance in students includes building cooperation between lecturers in building an attitude of religious tolerance in students, ensuring the socialization of religious tolerance, formulating school regulations or rules related to attitudes of tolerance between religious communities in the school environment and introducing the values ​​of religious tolerance are also included in the program to plan and implement learning in the classroom by adjusting to the topic